PENGARUH EFEKTIVITAS PENGGUNAAN, LOCUS OF CONTROL DAN KUALITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Ni Made Sulistiani; Kadek Dewi Padnyawati (UNHI Press, 2021)
The development of technology in the digital era is currently experiencing changes very quickly. As with the development of information technology through computers and other software that are designed so sophisticated to make it easier to share information between humans. In addition to the need for a good system, it is also necessary to have system users who have adequate capabilities, so that they can take full advantage of the system. Success of the comppany largely determineed the employee performance.The populations in this study were all employes at PT. PLN (Persero) Bali Distribution Main Unit, amounting to 159 people. The number of respondents used was 74 people consisting of 26 people in the Financial Sector (BIKEU), 17 people in the Human Resources Sector (BISDM) and 31 people in the Commercial Sector (BIAGA). The sampling methods use was purposivee samplings technic. Data obtained through distributing questionnaires with the data analysis technique used is multiple regression analysis using SPSS. Based on the results of multiple linear analysis, the regression equation Y = 4.784 + 0.485X1 + 0.243X2 + 0.709X3 + â‚¬ is obtained. The conclusion of the studies shows that the effectiveneess of used has a positive and significant effect on employee performance, locus of control has a positive and significant effect on employee performance, and the quality of the accounting information system has a positive and significant effect on employee performance. This shows that the four variables can improve employee performance.